Facile morphology controlled synthesis of nanostructured Co3O4 films on nickel foam and their pseudocapacitive performance. Issue 58 (31st May 2016) - Fan, Huiqing; Zhong, Yuan; Chang, Ling; Zhu, Shasha; Wang, Kai; Shao, Haibo; Wang, Jianming; Zhang, Jianqing; Cao, Chu-nan
Abstract : The as-synthesized 3D hierarchically porous Co3 O4 network film on nickel foam shows prominent pseudocapacitive performance. Abstract : Nanostructured transition metal oxides are a current investigation focus for supercapacitors. We herein report a facile solvothermal synthesis of nanostructured Co3 O4 films on nickel foam. The morphologies and dimensions of the Co3 O4 films can be effectively tuned by tailoring the solvent compositions in the solvothermal reaction solutions. The effect of solvent composition on the morphologies of nanostructured Co3 O4 films is analyzed. The 3D hierarchically porous Co3 O4 network film, which is synthesized in the solvothermal reaction solution with an intermediate ethylene glycol/water volume ratio (1 : 29), shows a markedly enhanced pseudocapacitive performance. The specific capacitances of the Co3 O4 network film electrode at the current densities of 0.870 and 17.391 A g −1 are 2817 and 1948 F g −1, respectively, revealing its large specific capacitance and excellent rate capability. Furthermore, the Co3 O4 network film electrode exhibits good electrochemical cycling stability with a specific capacitance of 1628 F g −1 after 3500 cycles at a current density of 4.348 A g −1 . The prominent pseudocapacitive performance of the Co3 O4 network film electrode can be attributed to its unique structural characteristics. The as-synthesized 3D hierarchically porous Co3 O4 network film with excellent pseudocapacitive performance demonstrates promising potential as a high-performance electrode for supercapacitors.